Independent Recruitment of Duplicated β-Subunit-Coding NAD-ME Genes Aided the Evolution of C4 Photosynthesis in Cleomaceae - Tronconi, Marcos A.; Hüdig, Meike; Schranz, M. Eric; Maurino, Veronica G. (Frontiers in Plant Science, 2020)
In different lineages of C4 plants, the release of CO2 by decarboxylation of a C4 acid near rubisco is catalyzed by NADP-malic enzyme (ME) or NAD-ME, and the facultative use of phosphoenolpyruvate carboxykinase. The co-option of gene lineages during the evolution of C4-NADP-ME has been thoroughly investigated, whereas that of C4-NAD-ME has received less attention. In this work, we aimed at elucidating the mechanism of recruitment of NAD-ME for its function in the C4 pathway by focusing on the eudicot family Cleomaceae. We identified a duplication of NAD-ME in vascular plants that generated the two paralogs lineages: α- and β-NAD-ME. Both gene lineages were retained across seed plants, and their fixation was likely driven by a degenerative process of sub-functionalization, which resulted in a NAD-ME operating primarily as a heteromer of α- and β-subunits. We found most angiosperm genomes maintain a 1:1 β-NAD-ME/α-NAD-ME (β/α) relative gene dosage, but with some notable exceptions mainly due to additional duplications of β-NAD-ME subunits. For example, a significantly high proportion of species with C4-NAD-ME-type photosynthesis have a non-1:1 ratio of β/α. In the Brassicales, we found C4 species with a 2:1 ratio due to a β-NAD-ME duplication (β1 and β2); this was also observed in the C3Tarenaya hassleriana and Brassica crops. In the independently evolved C4 species, Gynandropsis gynandra and Cleome angustifolia, all three genes were affected by C4 evolution with α- and β1-NAD-ME driven by adaptive selection. In particular, the β1-NAD-MEs possess many differentially substituted amino acids compared with other species and the β2-NAD-MEs of the same species. Five of these amino acids are identically substituted in β1-NAD-ME of G. gynandra and C. angustifolia, two of them were identified as positively selected. Using synteny analysis, we established that β-NAD-ME duplications were derived from ancient polyploidy events and that α-NAD-ME is in a unique syntenic context in both Cleomaceae and Brassicaceae. We discuss our hypotheses for the evolution of NAD-ME and its recruitment for C4 photosynthesis. We propose that gene duplications provided the basis for the recruitment of NAD-ME in C4 Cleomaceae and that all members of the NAD-ME gene family have been adapted to fit the C4-biochemistry. Also, one of the β-NAD-ME gene copies was independently co-opted for its function in the C4 pathway.